Front Cover: A Comprehensive Study on Tetraaryltetrabenzoporphyrins (Chem. Eur. J. 15/2020). Issue 15 (24th February 2020) - Ruppel, Michael; Lungerich, Dominik; Sturm, Sabrina; Lippert, Rainer; Hampel, Frank; Jux, Norbert
Abstract : Access to tetraaryltetrabenzoporphyrins (TATBP) in order to investigate them in material and life sciences has never been easier. The cover art describes the synthetic feasibility with a "TATBP tuning shop", which shows the change of the four meso aryl substituents to modify the performance of the molecule. The analysis of the large library (30 compounds), which is highlighted in the back, provides an elaborate idea about the influence of the aryl moiety on the properties (artwork by M.R. and D.L.). More information can be found in the Full Paper by D. Lungerich, N. Jux, et al. on page 3287 .